Exercise-induced adaptations in the kynurenine pathway: implications for health and disease management - Rangel, Marcus Vinicius dos Santos; Lopes, Karynne Grutter; Qin, Xuebin; Borges, Juliana Pereira (Frontiers in Sports and Active Living, 2025)
BackgroundTryptophan (TRP) metabolism through the kynurenine (KYN) pathway is influenced by inflammatory mediators, generating metabolites that regulate immune and inflammatory responses. Exercise has been proposed as a modulator of this pathway, but its role in health benefits and chronic disease management remains unclear.ObjectiveThis systematic review examines exercise-induced adaptations in the KYN pathway and their potential implications for health and disease management. Additionally, we identify key methodological considerations for future research.MethodsA structured search of PubMed/Medline, Web of Science, and Scopus was conducted up to October 2024 to identify clinical trials investigating the effects of exercise training on the KYN pathway.ResultsOf 2,795 articles initially found, 13 clinical trials involving 592 participants met the inclusion criteria. Most studies reported exercise-induced adaptations in the KYN pathway, particularly in cancer survivors. These adaptations appeared to be influenced by exercise intensity and duration. However, several methodological limitations were noted, and no trials included patients with metabolic or cardiovascular diseases.ConclusionsHere, we show that exercise training modulates the KYN pathway in both healthy and diseased populations, highlighting its potential for disease prevention and management. However, further randomized-controlled trials are needed to clarify its mechanisms and clinical applications, particularly in metabolic and cardiovascular diseases.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022351481, PROSPERO (CRD42022351481).